(untitled) - Eric V Linder (harlow, England, 1997)
The book comprises three parts: Part 1 presents a broad overview of the fundamental concepts, cosmological models and observational tests, and the history, evolution, and fate of the universe. Part 2 is a detailed assessment of the physics of the hot Big Bang model, while Part 3 introduces some of the concepts of ongoing research into the formation of structure in the universe
Keywords: cosmology